PERUBAHAN KOMPOSISI METIL ESTER AKIBAT KERUSAKAN PANAS PADA METIL ESTER SULFONAT DARI JARAK PAGAR - Sri Hidayati (Universitas Andalas, 2011)
Vol 5 No 1ABSTRACT Surfactant is a surface-active agent that can be produced by a chemical or biochemical synthesis. The most widely used anionic surfactant in surfactant flooding is linier alkyl benzene sulfonate (LAS) synthesized from petroleum material. The weaknesses of petroleum based surfactant are: it is made from nonrenewable resources, has very poor detergency in hard water and naturally are difficult to be degraded. These problems can be overcome by producing methyl ester sulfonate (MES) surfactant made from natural resources, such jatropha oil es methyl ester. Temperature is the important factor that should be performed in MES stability. The purpose of this research is to investigate the sulfonate group caused by temperature and degradation time. The result of thermal degradation tests of Methyl Ester Sulfonates showed that at temperature of 150 oC during 72 hours influenced the degradation of sulfonate group. It was indicated by decreasing peak of sulfonate formed at the wave number of 1250 – 1150 cm-1. The increased of temperature showed decreased ability of surfactant to stabilized of emulsion and surface tension. Keywords: methyl ester sulfonates, thermal degradation